Facets of mindfulness related to a change in anxiety following a mindfulness-based intervention. Issue 1 (2nd January 2016) - Mizera, Carin M.; Bolin, Rebecca M.; Nugent, William R.; Strand, Elizabeth B.
ABSTRACT: Mindfulness has been operationalized into five facets that can be measured: Observe, Describe, Act with Awareness, Nonjudgment, and Nonreactivity. The purpose of this literature review is to determine if any single facet of mindfulness is more robustly associated with a change in anxiety. Five studies measuring changes in mindfulness facets following a mindfulness-based intervention and their effects on anxiety symptoms were examined. The results of this review are inconclusive. No clear connection emerged based on the literature reviewed, though the facet of Nonjudgment may have a stronger relationship with a change in anxiety based on these studies.